Compromise - Knight, Jack, 1952- (New York : New York University Press, 2018)
"Childhood friends Juliet, Rebecca, Rose and Matthew grew up in a small village outside Dublin. Now privileged, wealthy and powerful, they appear to have it all. But when Juliet is involved in a suspicious accident and lies trapped between life and death at the bottom of a cliff, a secret that has been hidden for years threatens the seemingly perfect lives of the close-knit group. For the beautiful, fragile Rose, Juliet's accident draws unwanted attention to the sins of the past. For her husband, the ruthlessly ambitious Matthew, it removes a critical obstacle from the path of his political career. And as Rebecca discovers more about what happened to her friend, she begins to wonder if she ever knew the real Juliet ..."--Publisher description.
Preface / Jack Knight -- The problem of clean hands : negotiated compromise in lawmaking / Eric Beerbohm -- Third parties to compromise / Anton Ford -- The moral distinctiveness of legislated law / David Dyzenhaus -- On compromise, negotiation, and loss / Amy J. Cohen -- Compromise in negotiation / Simon Cábulea May -- Uncompromising democracy / Melissa Schwartzberg -- Democratic conflict and the political morality of compromise / Michelle M. Moody-Adams -- The challenges of conscience in a world of compromise / Amy J. Sepinwall -- Necessary compromise and public harm / Andrew Sabl -- Compromise and representative government : a skeptical perspective / Alexander Kirshner.
Includes bibliographical references and index.
Online resource (HeinOnline, viewed November 29, 2021).
eBooks on EBSCOhost
Keywords: Political ethics; Compromise (Ethics); Morale politique; Compromis (Morale); POLITICAL SCIENCE / General; Compromise (Ethics); Political ethics; Political ethics; Compromise (Ethics); Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.